RESPONSE OF ALMOND SEEDLING (PRUNUS AMYGDALUS) TO SPRAY OF AMINOPLASMAL, HUMIC ACID AND BORON. - M. A., Shaymaa; Ibrahim, Z. R.; Nabi, H. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study was conducted at the nursery of the College of Agricultural Engineering Sciences; University of Duhok, Kurdistan Region, Iraq, during growing season (2020) to evaluate the effects of foliar sprays of three concentrations of aminoplasmal (0, 50 and 100 ml.L-1), concentrations of humic acid (0, 100 and 200 ml.L-1) and boron (0, 50 and 100 mg.L-1) on vegetative growth and nutritional status of one year old almond seedling (Prunus amygdalus). The factorial experiment within randomized complete block design was used with three replicates. Foliar spraying applied at two times. First spray was carried out on 25th of April and the other on 27th of May. Results indicated that foliar spray of aminoplasmal at 100 ml.L-1 significantly increased all vegetative growth characteristics (stem length, stem diameter, number of branches/seedling, number of leaves / seedling, chlorophyll, leaf area, leaf fresh weight, leaf dry weight), and significantly increase leave nutritional status (N, P, K and B). Humic acid at conc. (200 ml.L-1) and boric acid at conc. (100 mg.L-1) cause significant increases in all studied traits. In combination, the triple interaction between 100 ml.L-1 aminoplasmal with 200 ml.L-1 humic acid and 100 mg.L-1 boron was the most affected one which surpassed significantly on the control treatment and other treatments. In general, in this study, it was discovered that treatments with aminoplasmal, humic acid and boron significantly increased vegetative growth and nutritional status of almond seedling.